Amphibia, Anura, Brachycephalidae, Ischnocnema verrucosa Reinhardt and Lütken, 1862: Distribution extension to northeastern Brazil - Orrico, Victor Goyannes Dill [UNESP] (My University, 2010)
Herein I present a new geographical record of Ischnocnema verrucosa Reinhardt and Lütken, 1862 for northeastern Brazil and briefly discuss the new record with a previous record of similar characteristics. © 2010 Check List and Authors.
Keywords: Amphibia; Anura; Brachycephalidae; Ischnocnema verrucosa